Long-term mortality in patients with ST-segment elevation myocardial infarction is associated with anti-citrullinated protein antibodies. (1st August 2017) - Hermans, Maaike P.J.; van der Velden, Daniel; Montero Cabezas, José M.; Putter, Hein; Huizinga, Tom W.J.; Kuiper, Johan; Toes, Rene E.M.; Schalij, Martin J.; Wouter Jukema, J.; van der Woude, Diane
Abstract: Background: Cardiovascular (CV) mortality is higher in patients with rheumatoid arthritis (RA), in particular when anti-citrullinated protein antibodies (ACPA) are present. Recently, ACPA have also been described in a cohort of patients without RA, but with coronary artery disease (CAD). It is however unknown if ACPA can consistently be found in patients with CAD, and if ACPA are associated with mortality in these patients. The purpose of this study was to assess the relationship between ACPA and long-term outcomes including mortality in patients with ST-elevation myocardial infarction (STEMI) without RA. Methods: All patients with STEMI from the MISSION! Intervention Study were analyzed. Patients with RA were excluded. The association between ACPA (anti-CCP3) at baseline and 10 year mortality and re-infarction was investigated. Results: In total, 29 (11%) of 275 included patients were ACPA-positive, substantiating the previous description of ACPA in CAD patients. Increased cumulative cardiac mortality was observed in ACPA-positive patients in comparison with ACPA-negative patients. Moreover, after correction for other associated factors, ACPA-positivity was associated with long-term mortality (HR 3.1 [CI 1.4–7.1] p -value = 0.01) and long-term combined endpoint of re-infarction and death (HR 2.4 [1.2–4.6] p -value = 0.01). Conclusion: In STEMI patients without RA, the presence of ACPA is independently associated with long-term mortality and the combined endpoint of re-infarction and death. ACPA in patients with and without RA might act as an independent pro-atherogenic factor.